MYOPIA AS A RISK FACTOR FOR OPEN-ANGLE GLAUCOMA : A SYSTEMATIC REVIEW - Yovita (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: In myopia, the eye has excessive light refraction power, refracting parallel rays in front of the retina when not accommodated. In myopia, the visual media focus is in front of the macula lutea. Too strong refraction, refractive myopia, or a lengthy eyeball can cause this. This condition produces long-distance hazy vision, or "nearsightness". Myopia is a natural eye growth variant that may or may not be inherited. Stress of accommodation and convergence and anomalies in the connective tissue linking the trabeculae cause myopia-related glaucoma. The aim: This article showed myopia as a risk factor for open-angle glaucoma. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 78 articles, whereas the results of our search on SagePub brought up 72 articles. The results of the search conducted for the last year of 2013 yielded a total 32 articles for PubMed and 19 articles for SagePub. In the end, we compiled a total of 16 papers, 10 of which came from PubMed and six of which came from SagePub. We included five research that met the criteria. Conclusion: Myopia has been identified as a potential risk factor for POAG and may also serve as a potential protective factor against the progression of POAG. The potential cause for the observed phenomenon could be attributed to the existence of myopia accompanied by a deficiency in the lamina cribrosa. This defect may contribute to a deceleration in the rate of visual field deterioration, as well as the advancement of POAG. Additional investigation into the underlying mechanisms is still required.